2013
DOI: 10.3747/pdi.2011.00109
|View full text |Cite
|
Sign up to set email alerts
|

Using a Multidisciplinary Training Program to Reduce Peritonitis in Peritoneal Dialysis Patients

Abstract: ♦ObjectivesThe present study evaluated the tool used to assess patients’ skills and the impact on peritonitis rates of a new multidisciplinary peritoneal dialysis (PD) education program (PDEP).♦MethodsAfter the University Hospital Ethics Committee approved the study, the educational and clinical records of PD patients were retrospectively analyzed in two phases. In phase I, an Objective Structured Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 36 publications
1
63
0
4
Order By: Relevance
“…179 Single center observational studies from different parts of the world, as well as multinational national registry studies have reported that the rates of PD-related infections have steadily decreased over the last 10-20 years. 180,[186][187][188][189][190][191][192][193] Within Australia, country-wide PD-related peritonitis rates fell significantly by 37% over a 5-year period from 0.62 episodes per patient-year in 2008 to 0.39 episodes per patient-year in 2013 after a concerted, multidisciplinary and multipronged national peritonitis reduction campaign involving quarterly audit and feedback of individual unit peritonitis rates, prioritization of peritonitis prevention trials by the Australasian Kidney Trials Network, updating national clinical practice guidelines on peritonitis, launching peritonitis guideline implementation projects, publishing of a call to action paper, establishment of a PD Academy to provide PD training to junior nephrologists and nursing staff, and development of a Home Dialysis Network to support home dialysis patients (http:// homedialysis.org.au/). 161,[180][181][182][183][184][185] These reductions have been variously attributed to the use of twin bag disconnection systems, implementation of mupirocin chemoprophylaxis protocols, topical exit site application of gentamicin, coprescription of nystatin or fluconazole with antibiotic therapy, improved training of PD patients and/or staff, and better identification and targeting of peritonitis risk factors.…”
Section: Peritonitismentioning
confidence: 99%
“…179 Single center observational studies from different parts of the world, as well as multinational national registry studies have reported that the rates of PD-related infections have steadily decreased over the last 10-20 years. 180,[186][187][188][189][190][191][192][193] Within Australia, country-wide PD-related peritonitis rates fell significantly by 37% over a 5-year period from 0.62 episodes per patient-year in 2008 to 0.39 episodes per patient-year in 2013 after a concerted, multidisciplinary and multipronged national peritonitis reduction campaign involving quarterly audit and feedback of individual unit peritonitis rates, prioritization of peritonitis prevention trials by the Australasian Kidney Trials Network, updating national clinical practice guidelines on peritonitis, launching peritonitis guideline implementation projects, publishing of a call to action paper, establishment of a PD Academy to provide PD training to junior nephrologists and nursing staff, and development of a Home Dialysis Network to support home dialysis patients (http:// homedialysis.org.au/). 161,[180][181][182][183][184][185] These reductions have been variously attributed to the use of twin bag disconnection systems, implementation of mupirocin chemoprophylaxis protocols, topical exit site application of gentamicin, coprescription of nystatin or fluconazole with antibiotic therapy, improved training of PD patients and/or staff, and better identification and targeting of peritonitis risk factors.…”
Section: Peritonitismentioning
confidence: 99%
“…International Society for Peritoneal Dialysis Guidelines recommend the inclusion of the concepts of adult learning principles in the curriculum for future PD trainers to facilitate the subsequent training of PD patients . Indeed, the two trials to date incorporated these principles within their curriculum; however, it has not been shown that this is a required component . The current survey demonstrated that adult learning principles are not widely incorporated in PD units around Australia, with less than 50% of PD units assessing patients' learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…En nuestra revisión se encontró una adherencia a la técnica de conexión del 87%, lo cual evidencia el trabajo de capacitación y educación continua con el paciente, la no adherencia es del 13% siendo similar al 10% reportado en la literatura [46][47][48][49][50][51][52] .…”
Section: Discussionunclassified